Building Peace in Diversity Based on Islam (Analysis of Hadith Musnad Ahmad 22391) - Jumari Jumari; Damanhuri Damanhuri (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2024)
Abstract: This study focuses on analyzing a hadith narrated by Imam Ahmad in Musnad Ahmad 22391, which emphasizes unity, integrity, and the rejection of discrimination based on lineage or descent. The topic of peace and unity is highly relevant in addressing the challenges of modern multicultural societies, where diversity in ethnicity, language, and religion often leads to conflicts. Previous studies have explored the concepts of peace and unity but lack a specific focus on analyzing hadith texts as foundational guidance. This research addresses that gap by examining the quality of sanad and matan of the hadith and contextualizing its message for contemporary applications. Using a qualitative approach with a content analysis method, the study analyzes the hadith’s authenticity and meaning, supplemented by references to Islamic scholarly texts. Data were collected through library research and interpreted systematically to understand its implications for fostering societal harmony. Findings reveal that the hadith underscores piety as the true measure of nobility, promoting mutual respect and coexistence while discouraging divisions based on heritage or status. These findings reinforce the role of Islamic teachings in fostering peace and security in multicultural settings. This study contributes to the academic discourse by highlighting the relevance of hadith in supporting societal harmony amidst diversity.